General principle - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2020)
As a general proposition and subject to these Principles, a foreign judgment in a commercial matter is entitled to recognition and enforcement. Meaning of “judgment”. For the purposes of these Principles, a judgment means a decision on the merits given by a court or tribunal. Judgments may be given different labels such as decisions, orders or decrees.